The effectiveness of Minimum Income schemes in the EU - Vanda Almeida; Silvia De Poli; Adrian Hernández (European Commission, Joint Research Centre (JRC), 2022)
Minimum Income (MI) schemes are essential to alleviate poverty and guarantee a last-resort safety net to households with insufficient resources. Assessing the effectiveness of MI schemes in poverty reduction is challenging. Studies based on survey microdata are usually subject to a bias because households with very low incomes tend to underreport benefit receipts. Studies based on microsimulation models tend to overestimate these benefits mainly due to lack of data on take-up and non-income eligibility conditions. In this paper, we attempt to tackle these challenges to provide an integrated and consistent evaluation of the effectiveness of MI schemes in the European Union (EU). We develop a simple method that calibrates the simulation of MI schemes in the microsimulation model EUROMOD to obtain a new 'closer to reality' baseline simulation of each EU Member State's scheme. We then use this corrected baseline to evaluate existing MI schemes, investigating their degree of coverage and adequacy, their poverty-alleviating effects and their overall cost. Finally, we explore the effects of possible (theoretical) reforms, implementing sequential changes to the levels of coverage and adequacy, towards eradicating the extent of extreme poverty. The main takeaways are that the contribution of MI support to poverty elimination is still rather limited in some EU countries and that action could be taken to increase coverage and adequacy at a relatively low financial cost.
Keywords: H53; I32; I38; 330; minimum income; coverage; adequacy; poverty; microsimulation; EUROMOD